2017
DOI: 10.1159/000485406
|View full text |Cite
|
Sign up to set email alerts
|

Permanently Hypoxic Cell Culture Yields Rat Bone Marrow Mesenchymal Cells with Higher Therapeutic Potential in the Treatment of Chronic Myocardial Infarction

Abstract: Background: The mismatch between traditional in vitro cell culture conditions and targeted chronic hypoxic myocardial tissue could potentially hamper the therapeutic effects of implanted bone marrow mesenchymal stem cells (BMSCs). This study sought to address (i) the extent of change to BMSC biological characteristics in different in vitro culture conditions and (ii) the effectiveness of permanent hypoxic culture for cell therapy in treating chronic myocardial infarction (MI) in rats. Methods: rat BMSCs were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Stimulation of coronary collateral formation provides a broad prospect for the treatment of CAD patients [39][40][41]. Various therapeutic angiogenesis attempts focused on VEGF and FGF to induce coronary collateral growth have been reported in recent decades [10,42,43], but none of them really works in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of coronary collateral formation provides a broad prospect for the treatment of CAD patients [39][40][41]. Various therapeutic angiogenesis attempts focused on VEGF and FGF to induce coronary collateral growth have been reported in recent decades [10,42,43], but none of them really works in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term hypoxic preconditioning enhanced the cardioprotective properties of bone marrow stem cells (BMSCs) and downregulated the expression of pro-inflammatory and pro-fibrotic cytokines, whereas the expression of anti-inflammatory and angiogenic cytokines was upregulated in MI tissue. Compared to normoxic conditions, hypoxic preconditioned BMSCs showed better clonogenic potential and cell proliferation [ 51 ]. In addition, the studies demonstrated the increased viability of BMSCs at the site of infarction, enhanced heart function, and an increase in VEGF and transforming growth factor-β (TGF-β) expression.…”
Section: Stem Cell Preconditioning For MI Treatmentmentioning
confidence: 99%
“…In addition, the studies demonstrated the increased viability of BMSCs at the site of infarction, enhanced heart function, and an increase in VEGF and transforming growth factor-β (TGF-β) expression. The latter proteins were associated with collagen deposition in fibroblasts via PI3K/Akt and TGF-β/mothers against decapentaplegic homolog 2 (SMAD2) pathways, and VEGF also promoted vascularization at the MI site [ 51 ]. Although preconditioning for 24 h significantly enhanced paracrine secretion and the survival of MSCs in post myocardial tissue through the regulation of autophagy, 48 h preconditioning diminished the expression of VEGF, basic fibroblast growth factor (bFGF or FGF2), hepatocyte growth factor (HGF), and insulin-like growth factor-1 (IGF-1) and enhanced the level of apoptosis and autophagy in tissue [ 52 ].…”
Section: Stem Cell Preconditioning For MI Treatmentmentioning
confidence: 99%
“…Significantly higher number of cells as well as increased viability of ADSC occurs in hypoxic conditions [93]. Rat bone marrow MSC cultured at 5% oxygen levels exhibited increased number of colonies and shorter population doubling time as compared to normoxic cultured cells [94]. Asadpoor Dezaki et al showed increased expansion, population doublings, viability and colony forming unit fibroblasts in a group cultured in 2.5% oxygen tension than normoxia group [95].…”
Section: Effect Of Hypoxia On Proliferative Potential Of Cellsmentioning
confidence: 99%